Preparation method and application of cold-adaptive catalytic nano-enzyme and paper-based gas probe
MnSn(OH) 6-23-E10 nanoenzyme prepared by sodium hydroxide etching solves the problem of reduced biological detection reaction efficiency in low temperature environments, realizes high sensitivity detection at room temperature to 0°C, and is applied in paper-based gas probes to detect H2S gas and pork freshness.
Patent Information
- Application Number
- CN202411985221.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-15
AI Technical Summary
In low-temperature environments, the reaction efficiency of traditional biological detection methods is significantly reduced, resulting in a decrease in detection sensitivity. The types of existing cold-adapted nanoenzymes are limited, making it difficult to meet the needs of low-temperature biosensors.
The perovskite hydroxide nanoenzyme MnSn(OH)6-23-E10 prepared by sodium hydroxide etching increases the oxygen vacancy of the material and increases the valence state of Mn, thereby improving its catalytic activity and cold adaptability.
The nanoenzyme maintains excellent oxidase-like catalytic properties at room temperature to 0°C, detects the sensitivity of S2-, ascorbic acid and alkaline phosphatases that are close to or better than commercial kits, and are successfully applied in paper-based gas probes to detect H2S gas and pork freshness.
Smart Images

Figure CN119819290A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of biosensors, and in particular to a preparation method and application of a cold-adaptive catalytic nanozyme and a paper-based gas probe. Background Art
[0002] It remains extremely challenging to reliably obtain bioanalytical results in cold regions and areas that require low-temperature operations, such as cold chain transportation. Most biological kits have an optimal detection temperature range. When the ambient temperature exceeds this value, the accuracy of the results will be affected. Traditional biological detection methods rely on biochemical reaction signal amplification, such as enzyme catalysis or nucleic acid amplification, to obtain sensitivity. However, low temperatures can significantly reduce the efficiency of these reactions, thereby reducing detection sensitivity. In addition, when the ambient temperature is low, the function of electronic sensors and detection equipment will also be seriously affected. Therefore, the development of bioanalytical technologies that adapt to low-temperature environments and improve detection work capabilities and compatibility have great research importance and application potential.
[0003] As a biocatalyst with high catalytic efficiency and strong substrate specificity, enzymes have been widely used in the field of analytical technology. They can not only significantly amplify the detection signal and have outstanding catalytic efficiency, but also effectively remove the interference of other substances in the detection process. However, the optimal catalytic temperature of most biological enzymes is within a narrow physiological range. As the temperature decreases, the catalytic ability of the enzyme is greatly weakened. At the same time, the cost of enzyme extraction, preparation and utilization is also high. Therefore, designing enzyme mimics that can maintain catalytic function at low temperatures and are inexpensive, and using them to develop bioanalytical tools is expected to provide new low-temperature adaptive biosensors.
[0004] Nanozymes refer to nanomaterials with enzyme-like catalytic properties. Due to their diversity and ability to be mass-produced, nanozymes may become a potential substitute for enzymes. Although the types and numbers of nanozymes discovered so far are large, the number of nanozymes that truly have excellent low-temperature catalytic ability is still very limited. Research on cold-adapted nanozymes is still in its early stages, and the only few examples currently available are mainly based on metal-organic frameworks (MOFs), single-atom components, metal oxides, and magnetoelectric coupling materials. At the same time, there are few reports on the use of cold-adapted nanozymes to construct low-temperature-resistant biosensors. For this reason, there is an urgent need to develop a cold-adapted catalytic nanozyme and systematically explore its low-temperature-resistant biological detection performance. Summary of the invention
[0005] In order to solve the above problems, the present invention provides a preparation method and application of a cold-adaptive catalytic nanozyme and a paper-based gas probe.
[0006] The present invention is achieved through the following technical solutions:
[0007] A cold-adaptive catalytic nanozyme, wherein the cold-adaptive catalytic nanozyme is a perovskite hydroxide etched by sodium hydroxide; the perovskite hydroxide is MnSn(OH)6; the etching temperature is 0°C to 100°C; and the etching time is 5min to 60min.
[0008] The preparation method of the cold-adapted catalytic nanozyme comprises the following steps:
[0009] Manganese acetate tetrahydrate and sodium citrate are dissolved in water to obtain solution A; tin tetrachloride pentahydrate is dissolved in ethanol to obtain solution B; the molar ratio of manganese acetate tetrahydrate, trisodium citrate and tin tetrachloride pentahydrate is 1:1-2:1-2.
[0010] Solution B is mixed with solution A, and stirred to obtain a mixture. A sodium hydroxide solution is added to the mixture at 0°C to 100°C, and the precipitate is collected by centrifugation, washed, and dried to obtain MnSn(OH)6; the volume ratio of the mixture to the sodium hydroxide solution is 8:1 to 2.
[0011] MnSn(OH)6 was dispersed in water, etched with sodium hydroxide solution, washed, centrifuged and dried to obtain MnSn(OH) 6-23-E10 , that is, cold-adapted catalytic nanozyme; the mass volume ratio of MnSn(OH)6 to sodium hydroxide solution is 15:2~3.
[0012] Preferably, the mixture is added to the sodium hydroxide solution at 23°C.
[0013] Preferably, the molar concentration of the sodium hydroxide solution during etching is 8M to 9M.
[0014] The cold-adapted catalytic nanozyme detects S at room temperature to 0°C. 2- , ascorbic acid or alkaline phosphatase, wherein the room temperature is 25°C.
[0015] A paper-based gas probe is constructed by using the cold-adaptive catalytic nanozyme.
[0016] The preparation method of the paper-based gas probe comprises dropping 1 mg / mL to 2 mg / mL of MnSn(OH) 6-23-E10 The solution was finally air-dried at room temperature.
[0017] Preferably, the MnSn(OH) 6-23-E10 The volume of the solution is 9 μL to 11 μL.
[0018] Preferably, the paper-based gas probe is placed in a sealed bag containing pork, and the freshness of the pork is detected by detecting H2S gas generated by the pork.
[0019] Compared with the prior art, the present invention has the following beneficial effects:
[0020] The present invention provides a cold-adaptive catalytic nanozyme, wherein the cold-adaptive catalytic nanozyme is a perovskite hydroxide etched by sodium hydroxide; the perovskite hydroxide is MnSn(OH)6; the etching temperature is 0°C to 100°C; and the etching time is 5min to 60min. The present invention uses sodium hydroxide to etch away part of Sn while keeping the raw material structure unchanged, thereby increasing the oxygen vacancies of the material. As a result of etching, the oxygen vacancies increase, which helps it to adsorb hydroxide ions, making the electronegativity of the material negative, which is beneficial to catalyze the positively charged substrate TMB. On the other hand, after sodium hydroxide etching, the valence state of Mn in the original structure appears in a higher 4-valence state. The activity of the nanozyme is enhanced by etching it with sodium hydroxide, and the catalytic property of the cold-adapted oxidase is made to be the same.
[0021] The cold-adaptive catalytic nanozyme was used to systematically test its ability to detect ions, small molecules, and proteins at room temperature to 0°C. It is worth mentioning that the cold-adaptive catalytic nanozyme has a good detection ability for S 2- The detection sensitivity of AA and ALP was close to that at RT, and for the detection of ALP, the sensitivity at 0°C was better than that of the commercial ALP kit.
[0022] In addition, the present invention utilizes MnSn(OH) 6-23-E10 A paper-based gas probe was successfully constructed and applied to the detection of H2S gas at room temperature to 0°C, and it can also detect the freshness of actual pork samples. The invention is simple to synthesize, low in cost, has good anti-interference and selectivity, and has been successfully applied to the determination of the freshness of actual pork samples. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0024] Figure 1 These are SEM images of CoSn(OH)6, MgSn(OH)6, FeSn(OH)6, MnSn(OH)6, CuSn(OH)6 and ZnSn(OH)6 of the present invention.
[0025] Figure 2This is a comparison chart of the oxidase-like activities of CoSn(OH)6, MgSn(OH)6, FeSn(OH)6, MnSn(OH)6, CuSn(OH)6 and ZnSn(OH)6 of the present invention.
[0026] Figure 2 In the figure, A is the relative oxidase-like activity of CoSn(OH)6, MgSn(OH)6, FeSn(OH)6, MnSn(OH)6, CuSn(OH)6 and ZnSn(OH)6, and the oxidase-like activity of MnSn(OH)6 is set as 100%. The inset is a photograph of the corresponding sample; B is the UV-visible absorption spectrum of the oxidase-like of CoSn(OH)6, MgSn(OH)6, FeSn(OH)6, MnSn(OH)6, CuSn(OH)6 and ZnSn(OH)6. C is the UV-visible absorption spectrum of CoSn(OH)6, MgSn(OH)6, FeSn(OH)6, MnSn(OH)6, CuSn(OH)6 and ZnSn(OH)6 itself.
[0027] Figure 3 The present invention is MnSn(OH) 6-0 ,MnSn(OH) 6-23 ,MnSn(OH) 6-54 ,MnSn(OH) 6-80 and MnSn(OH) 6-100 SEM image of .
[0028] Figure 4 The present invention is MnSn(OH) 6-0 、MnSn(OH) 6-23 、MnSn(OH) 6-54 、MnSn(OH) 6-80 and MnSn(OH) 6-100 Comparison results of oxidase activities.
[0029] Figure 4 In the equation, A is the relative oxidase activity of MnSn(OH)6 at different synthesis temperatures. 6-23 The oxidase activity of the samples is 100%, and the insets are photos of the corresponding samples from left to right; B is MnSn(OH) 6-0 、MnSn(OH) 6-23 、MnSn(OH) 6-54 、MnSn(OH) 6-80 and MnSn(OH) 6-100 UV-visible absorption spectra of oxidase-like enzymes.
[0030] Figure 5This is the PXRD spectrum result diagram of MnSn(OH)6 with different synthetic metals and at different synthesis temperatures in the present invention.
[0031] Figure 5 In the figure, A is the PXRD spectra of CoSn(OH)6, MgSn(OH)6, FeSn(OH)6, MnSn(OH)6, CuSn(OH)6 and ZnSn(OH)6; B is the PXRD spectra of MnSn(OH) 6-0 、MnSn(OH) 6-23 、MnSn(OH) 6-54 、MnSn(OH) 6-80 and MnSn(OH) 6-100 PXRD spectrum of .
[0032] Figure 6 The present invention is MnSn(OH) 6-23 and MnSn(OH) 6-23-E10 SEM images, PXRD spectra and comparison results of catalytic rates.
[0033] Figure 6 In which A is MnSn(OH) 6-23-E10 SEM image of MnSn(OH) 6-23 and MnSn(OH) 6-23-E10 PXRD spectrum of; C is MnSn(OH) 6-23 and MgSn(OH) 6-23-e10 The time kinetics of absorbance at 652 nm simulated oxidase catalytic activity. D is the initial velocity corresponding to that in C, V0.
[0034] Figure 7 The MnSn(OH) 6-23 Comparison of catalytic rate and potential.
[0035] Figure 7 In the figure, A is MnSn(OH) at different etching times 6-23 The time dynamics of absorbance at 652 nm to monitor the catalytic activity of the simulated oxidase; B is the initial velocity (V0) corresponding to Figure A; C is MnSn(OH) 6-23-E5 、MnSn(OH) 6-23-E10 、MnSn(OH) 6-23-E15 、MnSn(OH) 6-23-E30 、MnSn(OH) 6-23-E45 and MnSn(OH) 6-23-E60 Zeta potential.
[0036] Figure 8 The present invention is MnSn(OH) 6-23-E10Stability results at different temperatures and pH values.
[0037] Figure 8 In the experiment, A is the UV-visible spectrophotometer for the determination of MnSn(OH) at different temperatures. 6-23-E10 Oxidase activity assay; B is MnSn(OH) 6-23-E10 The relative oxidase activity at different temperatures is 25℃, which is 100%; C is the activity of MnSn(OH) at different pH values using a UV-visible spectrophotometer. 6-23-E10 Determination of oxidase activity; D is MnSn(OH) 6-23-E10 The relative oxidase activity at different pH values was 100% at pH 4.5.
[0038] Fig. 9 The present invention is MnSn(OH) 6-23-E10 Comparison of the catalytic activities of Pt nanoparticles at different temperatures.
[0039] Fig. 9 In which A is MnSn(OH) 6-23-E10 Comparison of the temperature-dependent oxidase-mimicking activities of Pt nanoparticles; B is MnSn(OH) 6-23-E10 Comparison of the normalized catalytic activity of Pt nanoparticles at different temperatures, A / A 37℃ , A 37℃ : Absorbance at 652 nm at 37°C.
[0040] Fig.10 The effects of different free radical scavengers on MnSn(OH) 6-23-E10 Effect of oxidized TMB.
[0041] Fig.11 The present invention is MnSn(OH) 6-23 and MnSn(OH) 6-23-E10 The results of peroxidase POD, oxidase OXD and catalase CAT-like activity assays.
[0042] Fig.11 In which A is MnSn(OH) 6-23 and MnSn(OH) 6-23-E10 Peroxidase POD and oxidase OXD-like activity determination; B is the comparison of POD and OXD-like activities corresponding to Figure A; C is the monitoring of MnSn(OH) 6-23 and MnSn(OH) 6-23-E10 Figure 5. Time kinetics of absorbance of catalase CAT at 240 nm; D is the initial velocity corresponding to Figure C, V0.
[0043] Fig.12 The present invention is MnSn(OH)6-23 and MnSn(OH) 6-2-E10 Comparison results of TEM-Mapping, XPS, ICP-MS and BET characterization.
[0044] Fig.12 In which A is MnSn(OH) 6-23 TEM and EDS element mapping diagram; B is the O, Mn, Sn element content corresponding to Figure A; C is the MnSn(OH) measured by ICP-MS 6-23 The element content of Mn and Sn in the 6-23 Mn 2p XPS spectrum; E is MnSn(OH) 6-23 BET surface area measurement; F is MnSn(OH) 6-2-E10 TEM and EDS element mapping diagram; G is the O, Mn, Sn element content corresponding to Figure A; H is MnSn(OH) measured by ICP-MS 6-2-E10 The element content of Mn and Sn in the 6-2-E10 Mn 2p XPS spectrum; J is MnSn(OH) 6-2-E10 BET surface area measurement.
[0045] Fig.13 The present invention is MnSn(OH) 6-23 and MnSn(OH) 6-2-E10 Comparison results of O and Sn spectra in the full XPS spectrum.
[0046] Fig.13 In which A is MnSn(OH) 6-23 XPS full spectrum of MnSn(OH) 6-23 O1s XPS spectrum; C is MnSn(OH) 6-23 Sn 3d XPS spectrum; D is MnSn(OH) 6-2-E10 XPS full spectrum; E is MnSn(OH) 6-2-E10 O1s XPS spectrum; F is MnSn(OH) 6-2-E10 Sn 3d XPS spectrum.
[0047] Fig.14 The present invention is MnSn(OH) 6-23 and MnSn(OH) 6-23-E10 Steady-state kinetics assay results.
[0048] Fig.14 In the figure, A is the effect of different concentrations of TMB on MnSn(OH) 6-23 Steady-state kinetics of MnSn(OH)6-23 Lineweaver-Burk plot of oxidase-like activity; C is the effect of different concentrations of TMB on MnSn(OH) 6-23-E10 Steady-state kinetics of MnSn(OH) 6-23-E10 Lineweaver-Burk plot of oxidase-like activity.
[0049] Fig.15 The present invention is MnSn(OH) 6-23-E10 Detection of S at RT and 0 °C 2- Comparison of ion capabilities.
[0050] Fig.15 In which A is MnSn(OH) 6-23-E10 Detection of S at RT 2- Schematic diagram of ions; B is a diagram containing TMB and MnSn(OH) 6-23-E10 At different concentrations of S 2- UV-visible absorption spectra with and without ions; C is MnSn(OH) 6-23-E10 Detection of S at 0°C 2- Schematic diagram of ions; D is a diagram containing TMB and MnSn(OH) 6-23-E10 At 0℃, different concentrations of S 2- UV-visible absorption spectra with and without ions; E is MnSn(OH) 6-23-E10 Detection of S at RT and 0 °C 2- Sensitivity comparison of ions; F is a linear graph in the concentration range of 1 to 20 μM at RT. G is a linear graph in the concentration range of 4 μM to 40 μM at 0°C; H is MnSn(OH) 6-23-E10 At RT and 0 °C, the 2- Detection limit of ions.
[0051] Fig.16 MnSn(OH) at RT 6-23-E10 For S 2- Selective studies of ions.
[0052] Fig.17 The present invention is MnSn(OH) 6-23-E10 Comparison of the ability to detect AA at RT and 0°C.
[0053] Fig.17 In which A is MnSn(OH) 6-23-E10 Schematic diagram of AA detection at RT; B is a diagram containing TMB and MnSn(OH) 6-23-E10 UV-visible absorption spectra in the presence and absence of different concentrations of AA; C is MnSn(OH) 6-23-E10Schematic diagram of AA detection at 0℃; D is a sample containing TMB and MnSn(OH) 6-23-E10 UV-visible absorption spectra of MnSn(OH) at RT and 0℃ in the presence and absence of different concentrations of AA. E is the absorption spectrum of MnSn(OH) at RT and 0℃. 6-23-E10 Comparison of sensitivity of detecting AA; F is the linear graph in the concentration range of 1μM to 30μM at RT; G is the linear graph in the concentration range of 1μM to 20μM at 0℃; H is MnSn(OH) 6-23-E10 Detection limits for AA at RT and 0 °C.
[0054] Fig.18 MnSn(OH) at RT 6-23-E10 Selective study of AA.
[0055] Fig.19 The present invention is MnSn(OH) 6-23-E10 Comparison of the ability to detect ALP at RT and 0°C.
[0056] Fig.19 In which A is MnSn(OH) 6-23-E10 Schematic diagram of ALP detection at RT; B is a schematic ... 6-23-E10 UV-visible absorption spectra in the absence and presence of different concentrations of ALP; C is MnSn(OH) 6-23-E10 Schematic diagram of ALP detection at 0℃; D is a schematic diagram of the detection of ALP ... 6-23-E10 UV-visible absorption spectra at 0℃ in the presence and absence of different concentrations of ALP; E is MnSn(OH) 6-23-E10 Comparison of sensitivity of ALP detection at RT and 0°C; F is 0.5-10U L at room temperature -1 Linear graph within the concentration range; G is 0.5 U·L at 0°C -1 ~6U·L -1 Linear plot over the concentration range; H is MnSn(OH) 6-23-E10 Detection limits for ALP at RT and 0 °C.
[0057] Fig. 20 MnSn(OH) at RT 6-23-E10 Selectivity for ALP detection.
[0058] Fig.21 The commercial ALP kit of the present invention detects S at RT and 0°C. 2- Comparison results of ion capabilities;
[0059] Fig.21In the figure, A is a schematic diagram of the commercial ALP kit for detecting ALP at RT; B is the UV-visible absorption spectrum measured by the ALP kit at RT; C is a schematic diagram of the commercial ALP kit for detecting ALP at 0°C; D is the UV-visible absorption spectrum measured by the commercial ALP kit at 0°C; E is a comparison of the sensitivity of the commercial ALP kit for detecting ALP at RT and 0°C; F is the UV-visible absorption spectrum of 0.5U·L at room temperature. -1 ~10U·L -1 Linear graph within the concentration range; G is 1U·L at 0℃ -1 ~10U·L -1 Linearity plot within the concentration range; H is the detection limit of ALP by the commercial ALP kit at RT and 0°C.
[0060] Fig. 22 This is a graph showing the ability comparison of the paper-based gas probe of the present invention to detect H2S gas in chemical reactions and meat deterioration processes at RT and 0°C;
[0061] Fig. 22 In the figure, A is the principle diagram of the paper-based gas probe for detecting H2S gas; the paper-based gas probe can detect H2S gas produced during chemical reactions and meat spoilage, showing obvious color changes at RT in B and 0℃ in C; D is the relationship diagram of the B value of the paper-based gas probe and the Na2S concentration at RT and 0℃; E is the relationship diagram of the B value of the paper-based gas probe and the pork weight at RT and 0℃. DETAILED DESCRIPTION
[0062] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively below, and preferred embodiments of the present invention are provided. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive.
[0063] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.
[0064] The inventive concept of the present invention is as follows:
[0065] The present invention provides a cold-adapted catalytic nanozyme, wherein the cold-adapted catalytic nanozyme is a perovskite hydroxide etched by sodium hydroxide; the perovskite hydroxide is MnSn(OH)6; the etching temperature is 0°C to 100°C; and the etching time is 5min to 60min. The present invention uses sodium hydroxide to etch away part of Sn while keeping the raw material structure unchanged, thereby increasing the oxygen vacancies of the material. As a result of etching, the oxygen vacancies increase, which helps it to adsorb hydroxide ions, making the electronegativity of the material negative, which is beneficial to catalyze the positively charged substrate TMB. On the other hand, after sodium hydroxide etching, the valence state of Mn in the original structure appears in a higher 4-valent state. Etching the nanozyme with sodium hydroxide enhances its oxidase-like activity and makes it have the catalytic property of cold-adapted oxidase. The present invention uses the MnSn(OH) 6-23-E10 It has excellent oxidase-like catalytic performance at RT to 0°C. It uses 3,3',5,5'-tetramethylbenzidine, or TMB, as a substrate and oxidizes it to produce a blue color with a characteristic UV absorption peak at 652nm. 2- ions, AA, ALP and H2S gas, due to their reducing properties, can reduce the blue solution to colorless, and the absorption peak at 652nm decreases or even disappears, thus achieving the purpose of S 2- , AA, ALP and H2S gas detection. By detecting different concentrations of S at RT to 0℃ 2- , AA, ALP, the detection range and detection limit are calculated, and quantitative detection can be performed.
[0066] Based on the same inventive concept, the present invention provides a paper-based gas probe, in which nanozymes are loaded on filter paper to make a paper-based gas probe, and the filter paper is placed in an environment filled with hydrogen sulfide gas (the actual sample pork will also produce hydrogen sulfide gas after being left for a long time). It is found that after 3,3',5,5'-tetramethylbenzidine, i.e. TMB, is dropped onto the filter paper, different shades of blue will appear according to different hydrogen sulfide concentrations, thereby realizing the detection of hydrogen sulfide gas and the freshness of pork.
[0067] The technical solution of the present invention will be further described below in conjunction with specific embodiments.
[0068] The sources of the reagents described in the following embodiments are as follows:
[0069] Ascorbic acid, i.e. AAP, and trisodium 2-phospho-L-ascorbate, i.e. AAP, were purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.
[0070] Alkaline phosphatase, ALP, was purchased from Shanghai Yuanye Biotechnology Co., Ltd.
[0071] Alkaline phosphatase detection kit (ALP Kit) was purchased from Bio-Technology Co., Ltd.
[0072] Unless otherwise specified, the experimental methods described in the following examples are all conventional methods; the reagents and materials described are all commercially available unless otherwise specified.
[0073] Room temperature is represented by RT in the present invention.
[0074] Example 1. Preparation method of cold-adapted catalytic nanozyme
[0075] Step 1: Dissolve 1 mmol of tetrahydrated manganese acetate CH3(COO)2Mn·4H2O and 1 mmol of sodium citrate Na3C6H5O7 in 70 mL of deionized water to obtain solution A. Dissolve 1 mmol of tin tetrachloride pentahydrate SnCl4·5H2O in 10 mL of ethanol to obtain solution B.
[0076] Step 2: Solution B and solution A are mixed, stirred for 30 minutes to obtain a mixture, 2M sodium hydroxide solution is added to the mixture under the condition of a water bath temperature of 23°C, after heat preservation for 1 hour, the precipitate is collected by centrifugation, washed twice with ethanol and deionized water, and dried at 60°C to obtain MnSn(OH)6. The volume ratio of the mixture to the sodium hydroxide solution is 8:1.
[0077] Step 3: Disperse 30 mg of MnSn(OH)6 in 9 mL of distilled water, then add 4 mL of 8 M sodium hydroxide solution at room temperature, stir at room temperature for 10 min to etch and increase the oxidase activity, wash with distilled water and ethanol, collect the residual powder by centrifugation, and dry at 60 ° C to obtain MnSn(OH) 6-23-E10 , which is the cold-adapted catalytic nanozyme.
[0078] Example 2. Preparation method of cold-adapted catalytic nanozyme
[0079] Step 1: Dissolve 2 mmol of tetrahydrated manganese acetate CH3(COO)2Mn·4H2O and 2 mmol of sodium citrate Na3C6H5O7 in 70 mL of deionized water to obtain solution A. Dissolve 2 mmol of tin tetrachloride pentahydrate SnCl4·5H2O in 10 mL of ethanol to obtain solution B.
[0080] Step 2: Solution B and solution A are mixed, stirred for 30 minutes to obtain a mixture, 2M sodium hydroxide solution is added to the mixture under the condition of a water bath temperature of 23°C, after heat preservation for 1 hour, the precipitate is collected by centrifugation, washed twice with ethanol and deionized water, and dried at 60°C to obtain MnSn(OH)6. The volume ratio of the mixture to the sodium hydroxide solution is 8:2.
[0081] Step 3: Disperse 30 mg of MnSn(OH)6 in 9 mL of distilled water, then add 6 mL of 9 M sodium hydroxide solution at room temperature, stir at room temperature for 10 min to etch and increase the oxidase activity, wash with distilled water and ethanol, collect the residual powder by centrifugation, and dry at 60 ° C to obtain MnSn(OH) 6-23-E10 , which is the cold-adapted catalytic nanozyme.
[0082] Comparative Example 1
[0083] CoSn(OH)6 was synthesized by the same method as step 1 and step 2 in the above embodiment 1, except that the metal compound used in solution A was different, namely cobalt nitrate hexahydrate Co(NO3)2·6H2O.
[0084] Comparative Example 2
[0085] MgSn(OH)6 was synthesized by the same method as step 1 and step 2 in the above embodiment 1, except that the metal used in solution A was different, namely magnesium nitrate hexahydrate Mg(NO3)2·6H2O.
[0086] Comparative Example 3
[0087] FeSn(OH)6 was synthesized by the same method as step 1 and step 2 in the above embodiment 1, except that the metal compound used in solution A was different, namely ferrous sulfate heptahydrate FeSO4·7H2O.
[0088] Comparative Example 4
[0089] CuSn(OH)6 was synthesized by the same method as step 1 and step 2 in the above embodiment 1, except that the metal compound used in solution A was different, namely copper sulfate pentahydrate CuSO4·5H2O.
[0090] Comparative Example 5
[0091] ZnSn(OH)6 was synthesized by the same method as step 1 and step 2 in the above embodiment 1, except that the metal compound used in solution A was different, namely zinc nitrate hexahydrate Zn(NO3)2·6H2O.
[0092] The performance of the perovskite hydroxides obtained in Example 1 and Comparative Examples 1 to 5 was characterized.
[0093] (1) Microscopic morphological characterization of CoSn(OH)6, MgSn(OH)6, FeSn(OH)6, MnSn(OH)6, CuSn(OH)6 and ZnSn(OH)6.
[0094] In order to prove the successful synthesis of CoSn(OH)6, MgSn(OH)6, FeSn(OH)6, MnSn(OH)6, CuSn(OH)6 and ZnSn(OH)6, SEM characterization was performed on them respectively. Figure 1 . Figure 1 It can be seen that CoSn(OH)6, MgSn(OH)6, FeSn(OH)6, MnSn(OH)6, CuSn(OH)6 and ZnSn(OH)6 are cubic with particle sizes of about 100nm to 450nm. At the same time, the PXRD of the above six perovskite hydroxides was detected. Figure 5 . Figure 5 As can be seen from Figure A, the shape of the XRD spectrum is consistent with the literature, proving its successful synthesis.
[0095] (2) Investigation of the oxidase activity of CoSn(OH)6, MgSn(OH)6, FeSn(OH)6, MnSn(OH)6, CuSn(OH)6 and ZnSn(OH)6.
[0096] To evaluate the mimetic oxidase activity of these perovskite hydroxides, the catalytic oxidation of a typical oxidase chromogenic substrate, 3,3',5,5'-tetramethylbenzidine, TMB, was monitored by UV-vis spectroscopy. Figure 2 . Figure 2 As can be seen from Figure A, after removing the background absorption interference of the material itself, only MnSn(OH)6 catalyzes the oxidation of TMB to produce blue. Figure B shows that the oxidized TMB has an obvious UV-visible absorption peak at 652nm, indicating that MnSn(OH)6 has the activity of simulating oxidase. In contrast, after TMB was mixed with the other five perovskite hydroxides, neither colored products nor characteristic absorption were produced, which shows that the Mn element is crucial to the oxidase activity of perovskite. Therefore, the Mn element was selected to synthesize the cold-adapted catalytic nanozyme, and the sodium hydroxide etching treatment in step three was no longer performed on Comparative Examples 1 to 5.
[0097] The water bath temperatures in Example 3, Example 4, Example 5 and Example 6 are 0° C., 54° C., 80° C. and 100° C. respectively, and the rest of the preparation method is exactly the same as that in Example 1.
[0098] The properties of MnSn(OH)6 obtained at different temperatures in Example 1 and Example 3 to Example 6 were characterized. MnSn(OH)6 at 0°C is marked as MnSn(OH) 6-0 , MnSn(OH)6 at 54°C is marked as MnSn(OH) 6-54 , MnSn(OH)6 at 80℃ is marked as MnSn(OH) 6-80 , MnSn(OH)6 at 100℃ is marked as MnSn(OH)6-100 In Example 1, MnSn(OH)6 at 23°C is marked as MnSn(OH) 6-23 .
[0099] (1) Microscopic morphology of MnSn(OH)6 obtained at different temperatures in Example 1 and Examples 3 to 6.
[0100] In order to prove the successful synthesis of MnSn(OH) in Examples 1 and 3 to 6, SEM characterization was performed. Figure 3 . Figure 3 It can be seen that the MnSn(OH)6 in Examples 1 to 5 is cubic and has a particle size of about 10nm to 20nm. At the same time, the PXRD patterns of the perovskite hydroxides synthesized at different water bath temperatures were detected. Figure 5 . Figure 5 As can be seen from Figure B, the shape of the XRD spectrum is consistent with the literature, proving its successful synthesis.
[0101] (2) Investigation of the oxidase activity of MnSn(OH)6 in Examples 1 and 3 to 6.
[0102] To evaluate the mimetic oxidase activity of these perovskite hydroxides, the catalytic oxidation of a typical oxidase chromogenic substrate, 3,3',5,5'-tetramethylbenzidine, TMB, was monitored by UV-vis spectroscopy. Figure 4 . Figure 4 As can be seen from Figure A, in contrast, when the water bath temperature is 23°C, the oxidase activity of the perovskite hydroxide synthesized in Example 2 is the highest, and the blue color produced is the deepest. As can be seen from Figure B, when the water bath temperature is 23°C, MnSn(OH)6 has an obvious UV-visible absorption peak at 652nm, which indicates that the oxidase activity of the perovskite hydroxide is best when the water bath temperature is 23°C.
[0103] The sodium hydroxide etching time in Example 7, Example 8, Example 9, Example 10 and Example 11 is 10 minutes, 15 minutes, 30 minutes, 45 minutes and 60 minutes respectively, and the rest of the preparation method is exactly the same as that in Example 3.
[0104] (1) MnSn(OH) obtained by etching with NaOH in Example 7 6-23-E10 Compared with the unetched MnSn(OH)6, the unetched MnSn(OH)6 is represented by MnSn(OH) 6-23 Indicates, see Figure 6 . Figure 6 In Figure A, it can be seen that MnSn(OH)6 can still maintain a cubic morphology after being etched by NaOH for 10 minutes, and the particle size is about 10nm~20nm. In Figure B, it can be seen that MnSn(OH)6 can still maintain a cubic morphology after being etched by NaOH for 10 minutes, and the particle size is about 10nm~20nm.6-23-E10 Still maintain its crystal structure. As can be seen from Figures C and D, after etching for only 10 minutes, MnSn(OH) 6-23-E10 The oxidase-like catalytic activity of the nanostructured samples increased by more than 100 times compared with the original rate before etching, indicating that etching with NaOH can indeed enhance its oxidase-like activity.
[0105] (2) Screening etching time
[0106] In order to explore the effect of etching time on the oxidase-like catalytic activity of nanozymes, the optimal etching time was further screened, and the MnSn(OH) 6-23-E10 The results are shown in Figure 7 . Figure 7 As can be seen in A and B, after etching for 5 minutes, 10 minutes, 15 minutes, 30 minutes, 45 minutes and 60 minutes, MnSn(OH) 6-23 The optimal etching time is 10 min. As shown in Figure C, this optimal etching time can be attributed to the MnSn(OH) 6-23-E10 , so that it can enhance its attraction to TMB, which is positively charged, through electrostatic interaction. Among them, 5 minutes is marked as MnSn(OH) 6-23-E5 , 10 minutes marked as MnSn(OH) 6-23-E10 , 15 minutes marked as MnSn(OH) 6-23-E15 , 30 minutes marked as MnSn(OH) 6-23-E30 , 45 minutes marked as MnSn(OH) 6-23-E45 and 60 minutes are marked as MnSn(OH) 6-23-E60 .
[0107] Example 12: Preparation method of paper-based gas probe
[0108] First, the back of the filter paper was divided into multiple 1 cm × 1 cm areas with a pencil; then, 9 μL of 1 mg / mL MnSn(OH) 6-23-E10 The solution was then air-dried at room temperature.
[0109] Example 13: Preparation method of paper-based gas probe
[0110] First, the back of the filter paper was divided into multiple 2 cm × 2 cm areas with a pencil; then, 10 μL of 1 mg / mL MnSn(OH) was dropped into the center of each area. 6-23-E10 The solution was then air-dried at room temperature.
[0111] Example 14: Preparation method of paper-based gas probe
[0112] First, the back of the filter paper was divided into multiple 3 cm × 3 cm areas with a pencil; then, 11 μL of 2 mg / mL MnSn(OH) 6-23-E10 The solution was then air-dried at room temperature.
[0113] Experimental Example 1: MnSn(OH) 6-23-E10 Performance Characterization
[0114] (1) MnSn(OH) 6-23-E10 Cold-adapted catalytic performance
[0115] Based on MnSn(OH) 6-23-E10 Excellent oxidase-like activity, the change of its catalytic performance with temperature was studied, see Figure 8 Through the UV-visible spectra at different temperatures in Figure A and the MnSn(OH) 6-23-E10 The oxidase activity at 25°C was set as 100%. Comparison of the activity changes at 0°C, 40°C, 60°C, 80°C, and 100°C showed that MnSn(OH) 6-23-E10 It has cold-adaptive catalytic performance and can maintain its excellent catalytic performance in the range of 0℃~37℃, but when the temperature rises to 80℃, its activity decreases significantly. In addition, it can be seen from Figures C and D that MnSn(OH) 6-23-E10 It has a wide pH adaptability range and can maintain oxidase-like activity in the pH range of 3.5 to 7.
[0116] (2) Comparison of MnSn(OH) 6-23-E10 Cold-adapted catalytic performance of Pt nanoparticles
[0117] Based on MnSn(OH) 6-23-E10 The cold-adapted catalytic performance of Pt nanoparticles was compared with that of Fig. 9 .Depend on Fig. 9 It can be seen that when the temperature drops from 37°C to 0°C, the activity of Pt nanozyme loses more than 30%, while MnSn(OH) 6-23-E10 The activity of the nanozyme only lost about 5%, which indicates that MnSn(OH) 6-23-E10 It has better adaptive catalytic performance than Pt nanoparticles.
[0118] (3) Exploring reactive oxygen species in nanozyme reactions
[0119] To further explore the reactive oxygen species (ROS) in the nanozyme reaction, we selected p-benzoquinone, β-carotene, and isopropanol to eliminate superoxide anions, singlet oxygen, and hydroxyl radicals that may be involved, see Fig.10 The results showed that superoxide anion may be MnSn(OH) 6-23-E10The main ROS catalyzed by
[0120] (4) Exploration of MnSn(OH) 6-23-E10 Other enzyme activities
[0121] In order to investigate the 6-23-E10 To investigate whether there are other enzyme activities besides oxidase, we compared MnSn(OH) 6-23 The activities of peroxidase POD and catalase CAT before and after etching are shown in Fig.11 . MnSn(OH) before and after etching 6-23 There is almost no POD activity, but its CAT-like catalytic activity is significantly enhanced after etching.
[0122] Experimental Example 2: Study on MnSn(OH) 6-23-E10 The generation of cold-adapted enzyme-like activity and the mechanism of activity enhancement
[0123] TEM elemental mapping, ICP-MS, XPS and BET measurement methods were used to analyze the differences in nanozymes before and after etching. Fig.12 and 13 . TEM spectra show that O, Mn, and Sn elements exist before and after etching, but their contents have changed, that is, the O content decreases, and the Mn and Sn contents increase. In addition, ICP-MS results show that after etching, the Mn content increases from 20.67% to 37.93%, and the Sn content decreases from 32.89% to 28.71%, which is consistent with the results of previous studies, that is, the O and Sn contents decrease after etching. XPS analysis was used to evaluate the changes in the valence state of the elements before and after etching. The Mn 2p spectra in Figures D and I show that after etching, the MnSn(OH) 6-23-E10 High-priced Mn 4+ , which is consistent with previous reports that high-valent Mn-O bonds are responsible for the excellent oxidase activity of nanozymes at low temperatures. Fig.13 The O1s spectra of B and E show that the perovskite hydroxide structure before etching contains lattice oxygen O L and hydroxyl ion OH - After etching, except for O L and OH - In addition, vacant oxygen O is generated V These newly generated O V It may also be MnSn(OH) 6-23-E10 Considering the importance of specific surface area to catalytic activity, the MnSn(OH) 6-23 and MnSn(OH) 6-23-E10 BET surface area. Fig.12 E and J, as well as Table 1, it can be seen that the surface area of BET after etching is increased from 102m2 g -1 Descend to 70m 2 g -1 , indicating that the specific surface area is not the factor that improves its activity.
[0124] Table 1 BET surface area and pore size
[0125]
[0126] Experimental Example 3: MnSn(OH) 6-23-E10 Kinetic studies
[0127] The standard Michaelis-Menten curve was observed and the kinetic parameters were derived: V = V max [S] / (K m +[S]), where V is the initial velocity, [S] is the substrate concentration, and V max is the maximum reaction rate, Michaelis constant K m For V max The substrate concentration at which the reaction occurs at half the concentration of Fig.14 As shown in Table 2, MnSn(OH) 6-23-E1 The catalytic efficiency (k cat / K m =3.3mM -1 s -1 ) and maximum reaction speed (V max =3.4×10 -11 mM -1 ) than the etched MnSn(OH) 6-23 (k cat / K m =7.2×10 -3 mM - 1 s -1 ,Vmax=6.5×10 -13 mM -1 ) is two orders of magnitude higher, which indicates that after etching, MnSn(OH) 6-23-E1 The catalytic performance is better than that of MnSn(OH) before etching 6-23 .
[0128] Table 2 Kinetic parameters of nanozymes with oxidase-like activity
[0129]
[0130] Experimental Example 4: MnSn(OH) 6-23-E10 For S 2- Ion detection, the specific method is as follows:
[0131] Different concentrations of Na2S, 0 μM, 1 μM, 2 μM, 3 μM, 4 μM, 5 μM, 10 μM, 20 μM, 40 μM, 60 μM, 80 μM and 100 μM, were mixed with 0.01 mg / mL MnSn(OH) 6-23-E10 and 500 μM TMB in a phosphate buffer at pH 4.5 at RT or 0°C for 5 minutes. The UV absorbance of the solution was measured at the characteristic absorption peak of 652 nm, and the AA was calculated based on the absorbance difference. 652: A is the absorbance of the solution without Na2S at 652nm, and the degree of change is related to S 2- It can be seen that at RT and 0°C, as S 2- With the increase of concentration, MnSn(OH) 6-23-E10 The UV absorbance at the characteristic absorption peak of 652nm gradually decreased, indicating that MnSn(OH) 6-23-E10 It can effectively detect S 2- , the results are as follows Fig.15 shown.
[0132] Experimental Example 5: MnSn(OH) 6-23-E10 For AA detection, the specific method is as follows:
[0133] Different concentrations of AA, 0 μM, 1 μM, 2 μM, 3 μM, 4 μM, 5 μM, 6 μM, 7 μM, 8 μM, 9 μM, 10 μM, 15 μM, 20 μM, 30 μM and 50 μM, were mixed with 0.01 mg / mL MnSn(OH) 6-23-E10 The mixture was reacted with 500 μM TMB in pH 4.5 phosphate buffer at RT or 0°C for 5 minutes. The UV absorbance of the solution was measured at the characteristic absorption peak of 652 nm, and the AA was calculated based on the absorbance difference. 652: A is the absorbance of the solution without AA at 652nm, and the standard curve is drawn against the AA concentration. It can be seen that at RT and 0℃, with the increase of AA concentration, MnSn(OH) 6-23-E10 The UV absorbance at the characteristic absorption peak of 652nm gradually decreased, indicating that MnSn(OH) 6-23-E10 It can effectively detect AA, and the results are as follows Fig.17 shown.
[0134] Experimental Example 6: MnSn(OH) 6-23-E10 For ALP detection, the specific method is as follows:
[0135] First, different concentrations of ALP, 0U·L -1 、0.5U·L -1 , 1U·L -1, 2U·L -1 、4U·L -1 、6U·L -1 、8U·L -1 and 10U·L -1 and 2 mM AAP were added to pH 8.0 PBS buffer and reacted at 37°C or 0°C for 30 min. Subsequently, 0.01 mg / m MnSn(OH) 6-23-E10 , pH 4.5 phosphate buffer and 500 μM TMB were incubated at RT or 0°C for 5 min, the UV absorbance of the solution was measured at the characteristic absorption peak of 652 nm, and the AA was calculated based on the absorbance difference. 652: A is the change in absorbance of the solution without ALP at 652nm and the standard curve of ALP concentration. It can be seen that at RT and 0℃, as the ALP concentration increases, MnSn(OH) 6-23-E10 The UV absorbance at the characteristic absorption peak of 652nm gradually decreased, indicating that MnSn(OH) 6-23-E10 ALP can be effectively detected, and the results are as follows Fig.19 shown.
[0136] Experimental Example 7: MnSn(OH) 6-23-E10 Low temperature adaptive detection of ions, small molecules and proteins
[0137] 7.1. Detection S 2- ion
[0138] 7.1.1 Detection Limit
[0139] By measuring MnSn(OH) 6-23-E10 Detection of different concentrations of S 2- UV-visible absorbance of ions at RT to 0°C, see Fig.15 and Table 3. MnSn(OH) 6-23-E10 At RT, S 2- It has good detection ability, its linear relationship is in the range of 20μM, and the detection limit is 0.68μM. At 0℃, although the decrease in temperature will cause MnSn(OH) 6-23-E10 The sensitivity is somewhat reduced, but the biosensor still has good S 2- The detection performance is linear in the range of 4μM to 40μM, and the detection limit is 1.50μM. The detection limit is calculated as 3σ / b, where σ is the standard deviation of the blank signal and b is the slope of the regression line. The results show that the low-temperature adaptive biosensor prepared in Example 7 of the present invention has the ability to detect S 2- The ability of ions.
[0140] Table 3 MnSn(OH) 6-23-E10 At RT and 0 °C for S2- Comparison with AA's detection capabilities
[0141]
[0142] 7.1.2 Anti-interference
[0143] MnSn(OH) 6-23-E10 For many common biological interfering ions, Zn 2+ Mg 2+ 、Co 2+ , Fe 3+ 、Na + ,La 3+ 、Lu 3+ 、Ce 3 + , Hg 2+ , Cu 2+ 、Ag + , Cu + 、Ni 2+ , Mn 2+ 、Cd 2+ , Pd 2+ , Ca 2+ Cr 2+ NH 4+ , the selectivity was evaluated, see Fig.16 The results show that these ions have a significant effect on S 2- The disturbance of the detection is negligible.
[0144] 7.2 Detection of AA
[0145] 7.2.1 Detection Limit
[0146] By measuring MnSn(OH) 6-23-E10 The UV-visible absorbance of different concentrations of AA at RT to 0°C was measured. Fig.17 and Table 3. MnSn(OH) 6-23-E10 Good detection ability of AA at RT, with a linear detection range of 1μM to 30μM and a detection limit of 0.12μM. The interference of temperature reduction on AA detection was further explored. Compared with the test results at RT, the cold-adapted biosensor had a higher detection sensitivity for AA at 0°C, with a linear range of 1μM to 20μM and a detection limit of 0.24μM. The detection limit was calculated as 3σ / b, where σ is the standard deviation of the blank signal and b is the slope of the regression line. The results show that the low-temperature adaptive biosensor prepared in Example 7 of the present invention has the ability to detect AA.
[0147] 7.2.2 Anti-interference
[0148] MnSn(OH) 6-23-E10The selectivity of various common biomolecules, Cys, His, Glu, Gal, UA, AA, GSH, VD2, VD3, CHOL, H2O2, CA, Glc was evaluated. Fig.18 The results showed that the interference of these bio-small molecules on AA detection was negligible.
[0149] 7.3. Detection of ALP
[0150] 7.3.1 Detection Limit
[0151] By measuring MnSn(OH) 6-23-E10 The UV-visible absorbance of ALP at different concentrations was measured at RT to 0°C. Fig.19 and Table 4. For protein detection, ALP was selected as the analyte because ALP can catalyze the decomposition of phosphate monoesters such as AAP to generate the reduced product AA. 6-23-E10 It has good detection ability for ALP at RT, and the linear detection range is 0.5U·L -1 ~10U·L -1 , the detection limit is 0.10U·L -1 The interference of temperature reduction on ALP detection was further explored. The detection sensitivity of ALP was higher at 0°C, with a linear range of 0.5 U·L -1 ~6U·L -1 , the detection limit is 0.39U·L -1 The detection limit was calculated as 3σ / b, where σ is the standard deviation of the blank signal and b is the slope of the regression line. The results show that the low-temperature adaptive biosensor prepared in Example 7 of the present invention has the ability to detect ALP.
[0152] Table 4 MnSn(OH) 6-23-E10 Comparison of ALP detection capabilities with ALP Kit at 37°C and 0°C
[0153]
[0154] 7.3.2. Anti-interference
[0155] MnSn(OH) 6-23-E10 For various substrates, ALP, GOX, AChE, Glu, Ala, Val, BSA, Na + , K + , Ca 2+ , the selectivity was evaluated, see Fig. 20 The results showed that the interference of these substrates on ALP detection was negligible.
[0156] 7.3.3 Comparison with commercial ALP detection kits
[0157] A commercial ALP assay kit (using p-nitrophenyl phosphate as a chromogenic substrate) was used as a control to compare its performance with that of MnSn(OH) 6-23-E10 Protein detection capabilities. Fig.21 and Table 4. The detection limit of the kit for ALP at room temperature is 0.078U·L -1 Compared with our detection limit of 0.10U·L -1 The detection limit of the kit for ALP at 0°C increased by 7.8 times. This shows that MnSn(OH) 6-23-E10 It has stronger tolerance to temperature, and its detection limit changes less at 0°C, which is lower than that of commercial kits, showing strong low-temperature adaptability detection capabilities.
[0158] Experimental Example 8: The paper-based gas probe prepared in Example 13 is used for H2S gas detection. The specific method is as follows:
[0159] Place the paper-based gas probe and a brown glass bottle containing different concentrations of Na2S and HCl in a sealed plastic bag and react under RI for 1 hour. After the reaction, take out the paper-based gas probe and dot the center area with 25mM TMB for reaction. Use the smartphone Xiaomi 11 to photograph the paper-based gas probe after the reaction, and then use Photoshop to extract the RGB values from the image for quantitative analysis. When measuring the ability to detect H2S gas at 0℃, the prepared reagent should be placed in a 0℃ refrigerator for pre-cooling in advance, and the entire reaction should be carried out in a 0℃ refrigerator. It can be seen that at RT and 0℃, as the H2S concentration increases, the blue area of the paper-based gas probe becomes lighter, indicating that the paper-based gas probe can effectively detect H2S gas. The results are shown in Fig. 22 As shown in B, C and D.
[0160] Experimental Example 9: Detection of H2S gas in practical applications
[0161] H2S gas is an important freshness indicator of meat during low-temperature transportation. This example uses the paper-based gas probe prepared in Example 13 to detect the H2S gas produced by the actual sample, that is, the smell of rotting pork. In this work, the generation of H2S gas mainly relies on two pathways: one is a chemical reaction, that is, the reaction of Na2S and HCl; the other is the natural decay of meat at room temperature. By observing the color changes on the paper with the naked eye, taking pictures with a smartphone and quantitatively analyzing its RGB color, see Fig. 22. The results show that the paper-based gas probe can successfully detect H2S gas at RT and 0°C. The low sensitivity of detecting H2S at 0°C may be due to the reduced reaction rate of Na2S and HCl at low temperatures, resulting in less H2S generation. Similarly, the low sensitivity of pork freshness detection at 0°C may be due to the fact that low temperatures inhibit the deterioration of meat, resulting in relatively low H2S concentrations. The results show that the paper-based gas probe prepared by the present invention has the ability to detect H2S gas and can be applied to the detection of the freshness of actual pork samples.
[0162] Experimental Example 10: The paper-based gas probe prepared in Example 13 was used to detect the freshness of pork. The specific method is as follows:
[0163] The pork was divided into 5 g, 10 g, 20 g, 30 g, and 50 g, sealed in a plastic bag, and placed at room temperature for 18 h. Then, the paper-based gas probe was placed in the bag and incubated at RT and 0 °C for 1 h. The paper-based gas probe was taken out and 10 μL of 25 mM TMB was added to its center. Finally, a mobile phone was used to take a photo, and the RGB values were extracted and analyzed using Photoshop. The freshness of the pork was successfully detected, and the test results are shown in B, C, and E in 22.
[0164] In summary, the present invention constructs a novel cold-adapted nanozyme MnSn(OH) 6-23-E10 S can be detected at RT and 0℃ 2- ions, ascorbic acid AA and alkaline phosphate ALP, and constructed a paper-based gas probe, which was applied to the detection of H2S gas under conditions of RT to 0°C, and can also detect the freshness of actual pork samples. The present invention uses easy-to-control multi-metal doping and simple synthesis of perovskite hydroxide as a template, and improves its catalytic activity through sodium hydroxide etching, so that it has cold-adaptive catalytic performance. During detection, TMB is used as a color substrate, and an oxidation reaction makes it appear blue and has a characteristic absorption peak at 652nm, while reducing substances can make the blue fade and the characteristic absorption peak decrease, thereby achieving S 2- ions, ascorbic acid AA, alkaline phosphatase ALP and H2S gas detection.
[0165] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0166] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A cold-adapted catalytic nanozyme, characterized in that: The cold-adaptive catalytic nanozyme is a perovskite hydroxide etched by sodium hydroxide; the perovskite hydroxide is MnSn(OH)6; the etching temperature is 0°C to 100°C; and the etching time is 5min to 60min.
2. The method for preparing the cold-adapted catalytic nanozyme according to claim 1, characterized in that: The following steps are involved: Manganese acetate tetrahydrate and sodium citrate are dissolved in water to obtain solution A; tin tetrachloride pentahydrate is dissolved in ethanol to obtain solution B; the molar ratio of manganese acetate tetrahydrate, trisodium citrate and tin tetrachloride pentahydrate is 1:1-2:1-2; Mix solution B with solution A to obtain a mixture, add a sodium hydroxide solution to the mixture at 0°C to 100°C, keep the mixture warm for reaction, collect the precipitate by centrifugation, wash, and dry to obtain MnSn(OH)6; the volume ratio of the mixture to the sodium hydroxide solution is 8:1 to 2; MnSn(OH)6 was dispersed in water, etched with sodium hydroxide solution, washed, centrifuged and dried to obtain MnSn(OH) 6-23-E10 , that is, cold-adapted catalytic nanozyme; the mass volume ratio of MnSn(OH)6 to sodium hydroxide solution is 15:2~3.
3. The method for preparing the cold-adapted catalytic nanozyme according to claim 2, characterized in that: The mixture was added with sodium hydroxide solution at 23°C.
4. The method for preparing the cold-adapted catalytic nanozyme according to claim 2, characterized in that: The molar concentration of the sodium hydroxide solution during etching is 8M to 9M.
5. The cold-adapted catalytic nanozyme according to claim 1 detects S at room temperature to 0°C 2- , ascorbic acid or alkaline phosphatase.
6. A paper-based gas probe, characterized in that: A paper-based gas probe is constructed using the cold-adapted catalytic nanozyme described in claim 1.
7. The method for preparing a paper-based gas probe according to claim 6, characterized in that: Drop 1mg / mL to 2mg / mL of MnSn(OH) on the paper-based carrier. 6-23-E10 The solution was finally air-dried at room temperature.
8. The method for preparing a paper-based gas probe according to claim 7, characterized in that: The MnSn(OH) solution is dripped into the center of a paper-based carrier with an area of (1 cm×1 cm) to (3 cm×3 cm). 6-23-E10 The volume of the solution is 9 μL to 11 μL.
9. Use of the paper-based gas probe according to claim 6 in detecting the freshness of pork at room temperature to 0°C.
10. The use according to claim 9, characterized in that: The paper-based gas probe is placed in a sealed bag containing pork, and the freshness of the pork is detected by detecting H2S gas generated by the pork.